Against Prevailing Currents: The History of Them Days Magazine in Labrador - Hallett, Vicki S. (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2019)
For more than four decades, Them Days magazine has portrayed Labradorians in their own words through publishing a quarterly periodical and multiple books about Labrador as well as creating a public archive. This article will focus on the historical aspects of the magazine’s inception and the challenges its creators faced as they built a storehouse of Labrador narratives that would represent the cultures that make Labrador unique and document a way of life considered to be in precipitous decline. It will also discuss how individuals, peoples, and even magazines must continually negotiate their identities through power relations in a settler-colonial state.